Characteristics of exposure to radioactive iodine during a nuclear incident - Zaletel Katja; Mihovec Anamarija; Gaberscek Simona (Radiology and Oncology)
During a nuclear accident, numerous products of nuclear fission are released, including isotopes of radioactive iodine. Among them is iodine-131, with a half-life of 8.02 days, which emits β radiation. For decades, it has been effectively and safely used in medicine. However, in the event of a nuclear accident, uncontrolled exposure can have harmful biological effects. The main sources of internal contamination with iodine-131 are contaminated air, food and water. The most exposed organ is the thyroid gland, where radioactive iodine accumulates via the Na+/I− symporter (NIS). NIS does not distinguish between radioactive iodine isotopes and the stable isotope iodine-127, which is essential for the synthesis of thyroid hormones. Exposure to radioactive iodine during a nuclear accident is primarily associated with papillary thyroid cancer, whose incidence begins to increase a few years after exposure. Children and adolescents are at the highest risk, and the risk is particularly significant for individuals living in iodine-deficient areas.